Factors associated with undiagnosed and overdiagnosed COPD. Issue 2 (23rd June 2016) - Gershon, Andrea S.; Hwee, Jeremiah; Chapman, Kenneth R.; Aaron, Shawn D.; O'Donnell, Denis E.; Stanbrook, Matthew B.; Bourbeau, Jean; Tan, Wan; Su, Jiandong; Victor, J. Charles; To, Teresa
Worldwide, studies have shown that about 60–86% of people with chronic obstructive pulmonary disease (COPD) have not been diagnosed, which represents a missed opportunity to decrease disease burden through optimal management, including smoking cessation support and prescription medications [1–3]. Overdiagnosed COPD is also common, with prevalence estimates ranging from 4% to 64% in the general population and primary care settings [4, 5]. Overdiagnosis can lead to unnecessary COPD treatments with their own risks and costs, poor health-related quality of life and missed detection and treatment of other diseases [6]. Several factors are associated with undiagnosed and overdiagnosed COPD http://ow.ly/4mW6lu